How Do Men and Women Perceive a High-Stakes Test Situation? - Leiner, Julia E. M.; Scherndl, Thomas; Ortner, Tuulia M. (Frontiers in Psychology, 2018)
The results of some high-stakes aptitude tests in Austria have revealed sex differences. We suggest that such discrepancies are mediated not principally by differences in aptitudes, skills, and knowledge but gender differences in test takers’ perceptions of the test situation. Furthermore, previous research has indicated that candidates’ evaluations of the fairness of the testing tool are of great importance from an institutional point of view because such perceptions are known to influence an organization’s attractiveness. In this study, we aimed to investigate how women and men perceive and evaluate certain aspects of a high-stakes test situation by using the results and evaluations of an actual medical school aptitude test (753 applicants; 59% women). Test takers voluntarily evaluated the test situation and rated specific aspects of it (e.g., the fairness of the selection tool) and provided information regarding their test anxiety immediately after they completed the 4-hour test. Data analyses indicated small, albeit significant sex differences in participants’ perceptions of the test. Men described the test situation as slightly giving more opportunity to socialize and possessing more opportunity to deceive than women did. Furthermore, the perception of the test situation did not directly predict the test results, but it served as a moderator for the indirect effect of test anxiety on test results. By contrast, there were significant direct effects but no indirect effects of situation perception on evaluations of the fairness of the selection tool: The more the test situation was perceived as a high-pressure situation, the lower the fairness ratings of the testing tool. Results were discussed with reference to gender roles and test fairness.